Skills in Using Effective Sentences in Writing Observation Report Texts for Grade VIII Junior High School Students - Kania Putri Lestari; Suhartono (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the use of effective sentences in observation report texts of eighth-grade students of Al-Chodidjah Tebuireng Integrated Junior High School. The study was conducted in the odd semester of the 2025/2026 academic year. The study population consisted of 22 eighth-grade students. From this population, students were divided into five groups of 4–5 students each, with a sample of 10 observation report texts or two groups being analyzed. The research data consisted of observation report texts written by students as a result of writing learning assignments. Data collection was carried out through written tests, while data analysis was carried out by identifying the use of effective sentences based on indicators of unity of ideas, economy of words, sentence cohesion, and accuracy of sentence structure. Data were analyzed using descriptive statistical calculations with the help of the SPSS program. The results showed that students' ability to use effective sentences was in the sufficient category. Students generally understood the basic structure of sentences, but their application in writing observation report texts was not optimal. There were still sentences that were too long, unnecessary repetition of words, imbalance in subject-predicate structure, and inconsistent use of spelling and punctuation. The main obstacles faced by students include difficulty choosing diction, poor understanding of sentence structure, the habit of writing branching sentences, and low metalinguistic awareness. These findings indicate the need to strengthen micro-language skills in learning to write observational report texts.